Analisis Faktor Pemeliharaan terhadap Produktivitas Kakao (Theobroma cacao L.) di Kabupaten Luwu - Andi Besse Poleuleng; Susi Indriani; Andi Ayu Nurnawati (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2026)
Sustainable cocoa productivity is largely determined by the quality of the implementation of crop maintenance techniques at the farmer level. Differences in cultivation practices, particularly in fertilization, pruning, sanitation, as well as pest and disease control, lead to considerable variation in cocoa productivity. This study aims to analyze the relationship between maintenance techniques and cocoa productivity in Luwu Regency. Data were collected through primary data (farmer interviews) and secondary data. Sampling was determined based on farmers who cultivate cocoa and have at least 5 years of experience. The number of respondents was calculated using the Slovin method, resulting in a total of 232 respondents. The analysis used was multiple linear regression, examining the effects of Fertilizer Dosage (X1), Fertilization Method (X2), Fertilization Frequency (X3), Fertilization Timing (X4), Pruning (X5), Sanitation (X6), and Pest and Disease Control (X7) on productivity (Y).The results showed that, simultaneously, cultivation techniques including fertilizer dosage, fertilization method, fertilization frequency, fertilization timing, pruning, sanitation, and pest and disease control have an effect on cocoa productivity. Partially, fertilizer dosage, fertilization frequency, pruning, and pest and disease control have a significant effect on cocoa productivity, with a coefficient of determination (R²) of 0.85.